DESIGN FEATURES OF MANAGEMENT SYSTEMS ENTERPRISES OF THE PETROCHEMICAL COMPLEX - N. V. Barsegyan (Вестник университета)
Restructuring, redesigning or designing the organizational management structure on a scientific basis at domestic petrochemical enterprises are tools for improving the management system in the context of transition to new management standards, which contributes to the most effective achievement of goals. The article summarizes and analyses methods and approaches for designing organizational management structures and methods for their evaluation. In the development strategy of petrochemical enterprises aimed at resource conservation and the development of new petrochemical products, flexible organizational management structures are recommended, the design of which requires the use of a set of methods with the integration of the advantages of each of them. For proper management decision-making, it is necessary to develop a balanced system of indicators, in connection with which the author proposes the key indicators that characterize the effectiveness of the management system – technological, managerial, economic. The paper develops the functional model of modernization of the organizational management structure according to strategy of development of the enterprise based on the IDEF0 methodology. The study proposes the model of lean strategy for the development of the organizational structure of petrochemical enterprise management, as the integration of business strategic management systems, production organization and personnel training, based on the project management approach.